2017
DOI: 10.1007/s10549-017-4263-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic factors, anthropometric measures, diet, and physical activity in long-term breast cancer survivors: change from diagnosis and comparison to non-breast cancer controls

Abstract: The prevalence of the metabolic syndrome and diabetes/pre-diabetes was significantly higher in BC survivors than in controls group, notably in those with lower levels of physical activity. Enhanced diabetes/metabolic syndrome screening and promotion of physical activity may be warranted in BC survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
1
18
1
Order By: Relevance
“…Four studies reported decreased absolute protein intake in BCS [16,18,20,21]; however, this may be a result of decreased EI, as two studies reported increased [17] or no change [18] in protein when expressed as percent of total EI. Changes in carbohydrate intake were inconsistent, with studies reporting increased [16][17][18], decreased [17,20,21], or no change [18] in carbohydrate intake expressed in absolute or relative terms.…”
Section: Dietary Intake In Breast Cancer Survivorsmentioning
confidence: 94%
See 3 more Smart Citations
“…Four studies reported decreased absolute protein intake in BCS [16,18,20,21]; however, this may be a result of decreased EI, as two studies reported increased [17] or no change [18] in protein when expressed as percent of total EI. Changes in carbohydrate intake were inconsistent, with studies reporting increased [16][17][18], decreased [17,20,21], or no change [18] in carbohydrate intake expressed in absolute or relative terms.…”
Section: Dietary Intake In Breast Cancer Survivorsmentioning
confidence: 94%
“…As summarized in Table 2, dietary changes were presented as nutrients and/or food groups. Five studies reported decreased EI [16][17][18]20,21] in BCS with concomitant decreased absolute fat intake (g/day) [16][17][18]20] in four studies and decreased relative fat intake (as a percent of total EI) [17,18,21] in three studies. Four studies reported decreased absolute protein intake in BCS [16,18,20,21]; however, this may be a result of decreased EI, as two studies reported increased [17] or no change [18] in protein when expressed as percent of total EI.…”
Section: Dietary Intake In Breast Cancer Survivorsmentioning
confidence: 97%
See 2 more Smart Citations
“…In other surveys objectively measuring PA, long-term adherence by women with BC to current recommendations was even lower, from 9.0 to 16.0 % [32,33]. Some studies have highlighted that although adherence to PA recommendations by women with BC was low, it was similar to adherence observed in women with no cancer history [34]. However, in the present study, compared with the pre-diagnosis situation, over half of our study sample had decreased or completely stopped PA five years later.…”
Section: Physical Activitymentioning
confidence: 93%